2014
DOI: 10.1124/jpet.114.217323
|View full text |Cite
|
Sign up to set email alerts
|

Anα-Acetoxy-Tirucallic Acid Isomer Inhibits Akt/mTOR Signaling and Induces Oxidative Stress in Prostate Cancer Cells

Abstract: Here we provide evidence that aATA(8,24) (3a-acetyloxy-tir-8,24-dien-21-oic acid) inhibits Akt/mammalian target of rapamycin (mTOR) signaling. aATA(8,24) and other tirucallic acids were isolated from the acetylated extract of the oleo gum resin of Boswellia serrata to chemical homogeneity. Compared with related tirucallic acids, aATA(8,24) was the most potent inhibitor of the proliferation of androgen-insensitive prostate cancer cells in vitro and in vivo, in prostate cancer xenografted onto chick chorioallant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 43 publications
0
32
0
2
Order By: Relevance
“…However, cancer cell lysosomes are more vulnerable to rupture, causing leakage of lysosomal contents and activation of apoptosis [211,212], posing a new option for therapeutic developments. El Gaafary et al [213] demonstrated that treatment with both αATA(8,24) (3α-acetyloxy-tir-8,24-dien-21-oic acid) and rapamycin resulted in accumulation of acidic vesicular organelles and inhibition of mTOR/Akt signalling. Interestingly, and in contrast with rapamycin, αATA(8,24) alone was able to destabilize lysosomal and mitochondrial membranes, and induce ROS (reactive oxygen species) production.…”
Section: Future Research Directionsmentioning
confidence: 98%
“…However, cancer cell lysosomes are more vulnerable to rupture, causing leakage of lysosomal contents and activation of apoptosis [211,212], posing a new option for therapeutic developments. El Gaafary et al [213] demonstrated that treatment with both αATA(8,24) (3α-acetyloxy-tir-8,24-dien-21-oic acid) and rapamycin resulted in accumulation of acidic vesicular organelles and inhibition of mTOR/Akt signalling. Interestingly, and in contrast with rapamycin, αATA(8,24) alone was able to destabilize lysosomal and mitochondrial membranes, and induce ROS (reactive oxygen species) production.…”
Section: Future Research Directionsmentioning
confidence: 98%
“…It is important to note that the yield content of ABS and EBS from B. serrata is about 30%. In addition to boswellic acids and their respective O-acetyl derivatives, B. serrata is also characterized by the presence of euphane and tirucallane triterpenes, especially tirucallic acids, as inhibitors of Akt/mTOR signalling pathway with potential immunomodulatory properties (Badria et al, 2003;Estrada et al, 2010;Zhang et al, 2013;El Gaafary et al, 2015). The well-known inhibitors of Akt/mTOR signalling such as tacrolimus or sirolimus (rapamycin) have been shown to exert neuroprotective properties against cerebral I-R injury (Furuichi et al, 2003;Chauhan et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…B. Temozolomid) und Bestrahlung, wie an Gliomzellen gezeigt wurde [23]. Von den bisher bekannten Inhaltsstoffen eines Boswelliaextraktes verfügen über eine Antitumorwirkung ▪ Acetyl-11-keto-β-boswelliasäure ▪ 11-Keto-β-boswelliasäure ▪ β-Boswelliasäure ▪ Acetyl-β-boswelliasäure ▪ Ursolsäure ▪ Ätherisches Öl aus dem Harz Kürzlich wurde eine Tirucalsäure aus Olibanum mit Antitumorwirkung beschrieben [39]. Diese hemmt die Akt1-Kinaseaktivität, die ein Signal für die Tumorentstehung darstellt.…”
Section: Wirkungen Auf Verschiedene Tumorzelllinienunclassified
“…Ihre Hemmung führt zur Unterbrechung des Zellzyklus. Eine solche wurde bei Prostatakarzinomzellen durch ein Isomer der Tirucalsäure, einem Inhaltsstoff eines Boswelliaharzes, beschrieben [39]. Über eine Hemmung von mTOR-Targets durch Acetyl-Lupeolsäure berichteten 2017 Schmidt et al [21].…”
Section: Signalwege Der Proliferationunclassified